Non-destructive high-throughput DNA extraction and genotyping methods for cotton seeds and seedlings - Zheng, Xiuting (BioTechniques, 2015)
Extensive use of targeted PCR-based genotyping is precluded for many plant research laboratories by the cost and time required for DNA extraction. Using cotton (Gossypium hirsutum) as a model for plants with medium-sized seeds, we report here manual procedures for inexpensive non-destructive high-throughput extraction of DNA suitable for PCR-based genotyping of large numbers of individual seeds and seedlings. By sampling only small amounts of cotyledon tissue of ungerminated seed or young seedlings, damage is minimized, and viability is not discernibly affected. The yield of DNA from each seed or seedling is typically sufficient for 1000 or 500 PCR reactions, respectively. For seeds, the tissue sampling procedure relies on a modified 96-well plate that is used subsequently for seed storage. For seeds and seedlings, the DNA is extracted in a strongly basic DNA buffer that is later neutralized and diluted. Extracts can be used directly for high-throughput PCR-based genotyping. Any laboratory can thus extract DNA from thousands of individual seeds/seedlings per person-day at a very modest cost for consumables (~$0.05 per sample). Being non-destructive, our approach enables a wide variety of time- and resource-saving applications, such as marker-assisted selection (MAS), before planting, transplanting, and flowering